Persistence and metabolism of fenthion in orange fruit - Minelli, Elizabeth V. [UNESP]; Cabras, Paolo; Angioni, Alberto; Garau, Vincenzo L.; Melis, Marinella; Pirisi, Filippo M.; Cabitza, Franco; Cubeddu, Mario (My University, 1996)
The persistence and metabolism of fenthion in orange fruit were studied in field conditions. The fenthion was transformed to fenthion sulfoxide and fenthion sulfone. Sunlight photodegradation experiments showed that this transformation is due to the action of sunlight. Residues were found only in the fruit peel. Fenthion showed a rapid degradation rate with a half-life of ca. 6 days. Fenthion sulfoxide was degraded more slowly with a half-life of ca. 14 days and represented the major residue. Fenthion sulfone was present in low quantities.
Keywords: Fenthion; Metabolism; Orange fruit; Persistence; Residues